Mathematical Model of Love Dynamics in the Story of the Romantic Legend of the Mandar Tribe - Rifandi, Muhammad; Apriyanto, Apriyanto; Alnisari, Alnisari (Journal of Mathematics and Applied Statistics, 2024)
In this study, the mathematical model of love is discussed based on the legend of the Mandar tribe area in West Sulawesi Province. Love is an active action / activity carried out by humans towards other objects, in the form of self-sacrifice, empathy, attention, affection, help, obey words, follow, obey, and want to do whatever the object wants. This study aims to determine the mathematical model for the dynamics of love in the story of two lovebirds contained in the legend of Mandar and determine the equilibrium point and analyze the stability of the mathematical model of their love dynamics so that simulations and interpretations of mathematical models of dynamics can be carried out. Based on the model obtained, it can be known how the dynamics of love that occur between kaco and cicci based on several possible cases that can occur between the two of them. By using maple software, an equilibrium point is obtained consisting of two types of equilibrium points, namely the equilibrium point of the mathematical model of love if there is no struggle from kaco  ' and the equilibrium point of the mathematical model of love if there is a struggle from kaco'.